2011
DOI: 10.1681/asn.2011040433
|View full text |Cite
|
Sign up to set email alerts
|

Net Intestinal Transport of Oxalate Reflects Passive Absorption and SLC26A6-mediated Secretion

Abstract: Mice lacking the oxalate transporter SLC26A6 develop hyperoxalemia, hyperoxaluria, and calciumoxalate stones as a result of a defect in intestinal oxalate secretion, but what accounts for the absorptive oxalate flux remains unknown. We measured transepithelial absorption of [14 C]oxalate simultaneously with the flux of [ 3 H]mannitol, a marker of the paracellular pathway, across intestine from wild-type and Slc26a6-null mice. We used the anion transport inhibitor DIDS to investigate other members of the SLC26 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
85
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 32 publications
3
85
1
Order By: Relevance
“…Of the three segments we examined in this study, the cecum exhibited the largest steady-state, DRA-dependent (J Role of paracellular oxalate transport. Our conclusion regarding the role of DRA in transcellular oxalate transport in the mouse intestine is strikingly different from the recent proposal of Knauf et al (27) that transepithelial oxalate absorption (J ms Ox ) is predominantly passive and paracellular in all major intestinal segments. The key observation in their report was that, in isolated, short-circuited segments of WT mouse duodenum, oxalate and mannitol permeabilities (P Ox and P Man , respectively) were numerically similar when measured in the MS direction, but P Ox Ͼ P Man when measured in the SM direction.…”
Section: Dra Mediates Oxalate and CLcontrasting
confidence: 99%
See 1 more Smart Citation
“…Of the three segments we examined in this study, the cecum exhibited the largest steady-state, DRA-dependent (J Role of paracellular oxalate transport. Our conclusion regarding the role of DRA in transcellular oxalate transport in the mouse intestine is strikingly different from the recent proposal of Knauf et al (27) that transepithelial oxalate absorption (J ms Ox ) is predominantly passive and paracellular in all major intestinal segments. The key observation in their report was that, in isolated, short-circuited segments of WT mouse duodenum, oxalate and mannitol permeabilities (P Ox and P Man , respectively) were numerically similar when measured in the MS direction, but P Ox Ͼ P Man when measured in the SM direction.…”
Section: Dra Mediates Oxalate and CLcontrasting
confidence: 99%
“…In their initial report (Table 2), WT duodenum exhib-ited a net secretion of oxalate (Ϫ73 pmol·cm Ϫ2 ·h Ϫ1 ), but a net oxalate absorption (ϩ28 pmol·cm Ϫ2 ·h Ϫ1 ) was revealed in the PAT1 KO mouse duodenum. As indicated below, this net absorptive flux reported in their PAT1 KO model was obtained using a sampling protocol that commenced 2 h earlier than that employed in the later report of Knauf et al (27). In WT mouse ileum, we previously observed (9) a small net secretion of oxalate under short-circuit conditions (Ϫ10 pmol·cm Ϫ2 ·h Ϫ1 ), but in PAT1 KO mouse ileum there was a very large net absorption (ϩ75 pmol·cm Ϫ2 ·h…”
Section: Dra Mediates Oxalate and CLmentioning
confidence: 74%
“…8 Dietary oxalate is an important source of exogenous oxalate and is absorbed by the intestinal epithelium via the paracellular pathway. 9 The liver is the main source of endogenous oxalate; however, under physiologic conditions, a small fraction of the bodily oxalate is derived from hepatic production. 10 Studies using slc26a6 2/2 mice showed that increased serum oxalate is the result of impaired intestinal excretion that, in turn, leads to increased filtered renal oxalate load and formation of Ca 2+ -oxalate stones.…”
Section: +mentioning
confidence: 99%
“…Slc26a6 mediates oxalate clearance via the intestine, 9 and urinary citrate chelates the Ca 2+ to reduce the free Ca 2+ available for binding to oxalate. 11 Citrate binds Ca 2+ at a higher affinity than does oxalate; 12 thus, in the presence of a high citrate concentration, Ca…”
Section: +mentioning
confidence: 99%
“…SLC26A6 expression in mouse intestinal tissue is highest in duodenum (18), and active oxalate secretion in this tissue is completely ablated in Slc26a6-null mice (7,9). In contrast to the evidence for active oxalate secretion in mouse duodenum, oxalate absorption in this tissue is predominantly, if not exclusively, passive and paracellular (9). However, no studies to date have addressed the nature of the basolateral membrane oxalate transport process that operates in series with SLC26A6 to mediate active oxalate secretion across mouse duodenum.…”
mentioning
confidence: 99%